Tropical Epidemiology: A System for Continuous Demographic Monitoring of a Study Population - Stephens, J.; Alonso, P. L.; Byass, P.; Snow, R. W. (Methods of Information in Medicine, 1989)
Epidemiologists in many developing countries, where official demographic services are unavailable, have to include some demographic functions in their work. The usual method of documenting a study population for epidemiological research in a developing country consists of three stages: mapping, enumeration and vital registration. This paper considers the last element of this process, detailing the development of a suitable data system and explaining how its implementation using microcomputers and a database management system can help in the creation of an on-line continuous vital registration system for a study population as an epidemiological tool. The issues covered are data collection, entry and analysis, and the advantages of such a system for use in epidemiological research in developing countries are also discussed.
Keywords: Data Collection; Microcomputers; Tropical Epidemiology; Demographic Monitoring